2001
DOI: 10.1364/ol.26.001949
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of axial strain, temperature, and transverse load by a superstructure fiber grating

Abstract: A novel and simple fiber-optic sensor based on a superstructure fiber grating for simultaneous measurement of temperature, axial strain, and transverse load is proposed and demonstrated. By measurement of the shift and split of broadband and narrow-band loss peaks, one can determine the temperature, axial strain, and transverse load simultaneously over the ranges 0 -140 Recently, long-period gratings (LPGs) have been demonstrated as individual sensors for temperature, strain, and transverse-load measurement, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 7 publications
0
29
0
2
Order By: Relevance
“…The sensors have the potential to be used to measure pressure and deformations in numerous environments, such as smart structures or composite materials in bridges or dams. (5,6) For these applications, different types of fiber gratings can be designed and fabricated according to the index modulation distribution and grating period design. (2) In general, a single channel fiber grating is more often used for sensing only one physical parameter by measuring the Bragg wavelength shift.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensors have the potential to be used to measure pressure and deformations in numerous environments, such as smart structures or composite materials in bridges or dams. (5,6) For these applications, different types of fiber gratings can be designed and fabricated according to the index modulation distribution and grating period design. (2) In general, a single channel fiber grating is more often used for sensing only one physical parameter by measuring the Bragg wavelength shift.…”
Section: Introductionmentioning
confidence: 99%
“…(3) On the basis of the codirectionality and the counterdirectional coupling of an SFBG, a fiber sensor with a single sensing component has been used to measure multiple parameters simultaneously, such as axial strain, pressure, temperature, and curvature. (4)(5)(6) In this study, a second-order SFBG was successfully fabricated for the first time. Then, we experimentally demonstrated that the refractive index (RI) sensitivity of this sensor is larger than that of the first-order SFBG.…”
Section: Introductionmentioning
confidence: 99%
“…Such a modulation can be achieved by periodically triggering on and off the light exposure along the fiber [7,8], which needs an accurate control of the light exposure time, power and location for each subgrating, and the apolization is obtained by multiple exposures with different power levels for different subgrating sections [9]. Alternatively, a specially designed amplitude mask can be employed together with the phase mask during the grating inscription process however, owing to the fixed modulation envelope, different amplitude masks have to be used to produce different modulation profiles [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…For FBGs inscribed in birefringent fiber, the pair of closely spaced Bragg wavelengths separates further when transverse strain is applied 13 ; use of two FBGs with different periodicities produces 4 separate Bragg peaks, enabling the measurement of all three strain directions and temperature, simultaneously. Transverse strain measurement has also been demonstrated using long period gratings 14 , π -phase-shifted gratings 15 and superstructure gratings 16 . Previously we had reported on the effect of transverse strain on features in FBG spectra at 2/3 of the Bragg wavelength 17 , which are now understood 11 to be the 3 rd harmonic of a grating with Λ = Λ pm , in which the response depends upon the fiber orientation 18 .…”
Section: Introductionmentioning
confidence: 99%